Morpho-Molecular Diversity of Cashew Nut (Anacardium occidentale L.) Germplasm of Bangladesh (Plant Tissue Culture and Biotechnology, 2022)
The present investigation was conducted to identify the genetic variability in morphological characteristics among 12 cashew nut germplasm of Bangladesh. The morphological parameters such as nut length, width, single nut weight, and 100-nut weight varied significantly (p ≤ 0.01) among the germplasm studied. The shape and color of the cashew nuts and cashew apples were also variable. The RAPD analysis of the germplasm showed 71.43% polymorphism on average. The cluster analysis results revealed two distinct groups; cluster-I was made up of two genotypes, GP-7 and GP-8, while cluster-II consisted of ten genotypes. The maximum genetic distance (0.50) was exhibited between GP-4 and GP-8, while the minimum (0.107) was between GP-1 and GP-2, and between GP-2 and GP-3. The results of nut morphological characteristics and genetic relationships in cashew nut germplasm may be utilized in describing of new varieties and for plant improvement programs.Plant Tissue Cult. & Biotech. 32(2): 167-180, 2022 (December)